PERAN LEVERAGE SEBAGAI PEMODERASI: REVALUASI ASET TETAP, KEBIJAKAN DIVIDEN, NILAI PERUSAHAAN - Irham Salman; Amrie Firmansyah; Meicha Rizka Widyaningrum (Jurnal Magister Akuntansi Trisakti, 2020)
The firm value is closely related to the market's reaction to the information provided by management so that such information can influence investor behavior. This study is aimed to examine the effect of the revaluation of fixed assets and dividend policies on firm value. In addition, this study uses leverage as a moderation variable. This study employs a quantitative method with cross-sectional data. The data used in this study is secondary in the form of corporate financial statements registered in the Indonesian Stock Exchange (BEI) of the basic and chemical industry sectors from 2014 to 2016. Data obtained from the official website of the Indonesian Stock Exchange (BEI) through the site Http: / /www.idx.co.id. Sampling in this study uses purposive sampling method, so the final sample in the study is 34 observations. This study suggests that asset revaluation is negatively association with firm value, while dividend policy is not associated with firm  value. Furthermore, leverage successfully reinforces the negative impact of revaluation of fixed assets on firm value. Alson, leverage strengthens the influence of dividend policies that previously had no significant impact, becoming a significant positive impact on firm value. The results of this study show that financial report information can be used by investors in making investment decisions in the capital market, especially in relation to information on the revaluation of fixed assets conducted by the company.